An Active Pixel‐Matrix Electrocaloric Device for Targeted and Differential Thermal Management. Issue 15 (4th March 2023) - Bai, Peijia; Zhang, Quan; Cui, Heng; Bo, Yiwen; Zhang, Ding; He, Wen; Chen, Yongsheng; Ma, Rujun
Abstract: More than 55% of electronic failures are caused by damage from localized overheating. Up to now, there is still no efficient method for targeted temperature control against localized overheating. Although some existing thermal management devices handle this issue by full coverage cooling, it generates a lot of useless energy consumption. Here, a highly efficient pixel‐matrix electrocaloric (EC) cooling device is reported, which can realize a targeted and differential thermal management. The modified poly(vinylidene fluoride‐tertrifluoroethylene‐chlorofluoroethylene) reaches a large adiabatic temperature change of 7.8 K and is more suitable for thermal transfer and electrostatic actuation at high frequencies. All active pixels in the EC cooling device exhibit a stable temperature span of 4.6 K and a heat flux of 62 mW cm ‐2, which is more than twice that of the one‐layer EC device. Each refrigeration pixel can be independently controlled and effectively cooled down the localized overheating site(s) in situ. The surface temperature of the simulated central processing unit decreases by 33.2 K at 120 s after applying this EC device. Such a compact, embeddable, low cost, and active solid‐state pixel‐matrix cooling device has great potential for localized overheating protection in microelectronics. Abstract : A highly efficient pixel‐matrix electrocaloric (EC) cooling device is demonstrated on which each refrigeration pixel can be independently controlled and can effectively cool down the localized overheating on microelectronics in situ as needed. All active pixels in the EC cooling device exhibit a stable temperature span of 4.6 K and a heat flux of 62 mW cm ‐1 .